The Therapeutic Effect and Clinical Outcome of Immune Checkpoint Inhibitors on Bone Metastasis in Advanced Non-Small-Cell Lung Cancer - Asano, Yohei; Yamamoto, Norio; Demura, Satoru; Hayashi, Katsuhiro; Takeuchi, Akihiko; Kato, Satoshi; Miwa, Shinji; Igarashi, Kentaro; Higuchi, Takashi; Yonezawa, Hirotaka; Araki, Yoshihiro; Morinaga, Sei; et al. (Frontiers in Oncology, 2022)
Introduction: In advanced non-small-cell lung cancer (NSCLC), immune checkpoint inhibitors (ICIs) have been reported a better treatment outcome on primary lesions, however, the therapeutic effect on bone metastases has not been clarified. This study investigates the therapeutic effect of ICIs on bone metastases in advanced NSCLC. Methods: The data of patients with advanced NSCLC, treated with ICIs from 2016 to 2019 at our hospital, were analyzed. The therapeutic effects of ICIs on primary lung and metastatic bone lesions, concomitant use of bone modifying agents (BMA), treatment outcomes, and frequency of immune-related adverse events (irAEs) and skeletal-related events (SREs) were investigated. Results: A total of 29 patients were included (19 men and 10 women; mean age, 64.2 years). Among the ICIs, pembrolizumab was the most used (55.2%), and concomitant use of BMA was prevalent in 21 patients (zoledronic acid=1, denosumab=20). The therapeutic effect was partial response (PR) in 10.3% (n=3) on primary lung lesions by RECIST 1.1, complete response (CR) in 6.9% (n=2) and PR in 17.2% (n=5) on bone metastatic lesions by MDA criteria. ICIs suppressed the progression of bone metastasis in 21 cases (72.4%). All patients in CR and PR were treated with pembrolizumab and denosumab. SREs and irAEs were developed in 3.4% (n=1) and 20.7% (n=6), respectively. The median survival time after treatment with ICIs was 11.0 months. Concomitant therapy with ICIs and denosumab significantly prolonged the overall survival compared to ICI-only therapy (16.0 months vs. 2.5 months, p<0.01). Conclusions: This study showed that treatment with ICIs may successfully suppress the progression of bone metastasis in advanced NSCLC. Pembrolizumab with denosumab had the highest therapeutic effect on both primary lung lesions and bone metastases. Systemic treatment with this combination and conservative treatment of bone metastasis could be one of the options in the treatment of advanced NSCLC.